2023
DOI: 10.4102/hts.v79i2.8129
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the identity and economic sustainability of the Church: Case of AOG BTG in Zimbabwe

Abstract: With burgeoning economic challenges that have been hard-pressing Zimbabwe for more than a decade, most Zimbabwean classical Pentecostal churches who do not strategically multiply their revenue in reciprocal correspondence with God-given resources have been disabled and forced to narrow their missionary focus towards proclamation of the gospel and neglected other dimensions of mission, such as diakonia. The partial focus on the gospel in word without corresponding deeds portrayed an exclusively Salvationist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This is why Ezenweke and Kanu (2012, p. 110) avow that the contribution of the Church to national economic development is significant. Tagwirei and Masango (2023) found that churches that operate without economic sustainability often fail to meet the costs of the integral mission. Similarly, Ezenweke and Kanu (2012) commend the Church for showcasing its mandate and its capacity to contribute to national development.…”
Section: Working To Achieve Economic Sustainabilitymentioning
confidence: 99%
“…This is why Ezenweke and Kanu (2012, p. 110) avow that the contribution of the Church to national economic development is significant. Tagwirei and Masango (2023) found that churches that operate without economic sustainability often fail to meet the costs of the integral mission. Similarly, Ezenweke and Kanu (2012) commend the Church for showcasing its mandate and its capacity to contribute to national development.…”
Section: Working To Achieve Economic Sustainabilitymentioning
confidence: 99%